Regional distribution centres - Greenslade, D (Journal of sterile services management, 1987)
Regional Distribution Centres are designed for all items of a volume nature. While medical and surgical items are a component, so too are textiles, food, stationary, etc. An RDC is a complete entity. We recognise, however, that medical and surgical items need special consideration. It is necessary to produce conditions that are equal to, if not better than, that of the suppliers. The Scientific and Technical Branch of the DHSS have inspected the Mersey RDC. They have made a number of recommendations to bring it up to GMP standard for the storage and handling of sterile goods. Most of these have been implemented, although some are still awaited. Suppliers are obliged to meet these standards so I feel we should be no different. My message to you is that Regional Distribution Centres certainly work, provided that there is open and frank debate and that all concerned are fully involved